EVALUATION OF THE EFFICIENCY OF SORBENTS-CATALYSTS FOR THE PURIFICATION OF WATER FROM MANGANESE COMPOUNDS - GOMELYA, Mukola; TRUS, Inna; TVERDOKHLIB, Mariia; RUDENKO, Oleksandra (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The condition of sources and central water supply systems does not guarantee the required quality of drinking water. A large part of the population of Ukraine uses drinking water that does not meet hygienic requirements according to various indicators. Manganese compounds are quite often present in natural waters. Their quantitative content can vary in a wide range, depending on the region, it can be 5-6 mg/dm3. Manganese in underground waters is presented as ion Mn2+, salts of which are soluble. To remove manganese from water one should transfer it to insoluble state by oxidation. Today, there are a number of typical technologies of demagnetization of water. Many works have also been published which describe the purification of water from manganese ion.  It is worth noting that with a high content of manganese compounds in water, their removal is a rather difficult task. Removal of manganese compounds from water can be implemented using the ion exchange method, which consists of filtering water through loading in salt or acidic form. At the same time, softening and desalination of water can occur simultaneously. Therefore, the ion exchange method should be used for comprehensive water purification, softening, and removal of manganese compounds.In order to study the oxidizing capacity of catalytic loading with respect to manganese compounds in water were used as a catalytic load KU-2-8 cationite modified with magnetite and manganese oxide in H+, Na+, and Ca2+ forms. To modify cationite with magnetite under static conditions, it was treated with a solution containing a mixture of Fe2+ and Fe3+ ions in a ratio of 1:2. The research was also carried out on the preparation of catalysts based on cationites by modifying them with manganese compounds.The purpose of this article  is to evaluate the efficiency of manganese removal from water when using a catalyst sorbent. The article presents the results of research on water purification from manganese compounds using sorbents-catalysts modified with iron and manganese compounds. It was established that in static and dynamic conditions, complete extraction of manganese ions can be achieved using sorbents based on polymer resin and magnetite. When using cation exchange resin modified with magnetite, the removal of Mn2+ ions from aqueous solutions occurs both due to ion exchange, regardless of the form of the ion exchanger, and due to oxidation on the catalyst (magnetite) in the presence of dissolved oxygen.  Modified cation exchange resin in Na+ form leads to the extraction of manganese due to sorption and oxidation of Mn2+. In this case, sorption of calcium and magnesium ions, which is known to be accompanied by an increase in pH. The pH of the medium increased, which increased the efficiency of oxidation of manganese ions on magnetite. Under  these  conditions,  the  sorbent  catalyst  provides  complete  removal  of manganese ions due to catalytic oxidation and sorption of manganese ions on magnetite.
Keywords: manganese ions; magnetite; sorbent; catalyst; cationite; aeration